New applications of rhodium-catalysed hydroacylation - Iwumene, NUN (2022)
This thesis describes the development of two new rhodium-catalysed hydroacylation methods. The first involves a one-pot hydroacylation/thio-conjugate addition cascade towards the synthesis of fully saturated sulfur heterocycles. The second exploits novel β-sulfonyl aldehydes to access β-keto-sulfones and sulfonamides.